PERSPEKTIF GURU TERHADAP PENDIDIKAN GENDER DI MADRASAH TSANAWIYAH - Hamise, Hamise (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2023)
This study aims to explore teachers' perspectives on gender education in Madrasah Tsanawiyah. Using a qualitative approach, data was collected through in-depth interviews, classroom observations, and documentation analysis. The findings suggest that teachers' understanding of gender education varies, with some teachers showing a deep understanding while others still feel confused. The implementation of gender education in the classroom also faces various challenges, including resistance from students and parents as well as limitations in adequate resources and training. Nonetheless, gender education has shown a positive impact on students' attitudes, behaviors, and understandings. Teachers who have the support of madrassas and communities tend to be more successful in teaching this topic. This study emphasizes the importance of holistic and continuous support from various parties to improve the effectiveness of gender education in madrasas.